Transcription factor EB enhances macrophage autophagy and reverses endotoxin tolerance - YANG Ting; YANG Ting; LIU Xin (陆军军医大学学报)
Objective‍　‍To investigate the role of transcription factor EB (TFEB) in endotoxin-tolerant macrophages. Methods‍　The RAW264.7 cells were divided into blank group (DMEM medium), LPS 5 group (5 ng/mL LPS treatment for 4 h), LPS 100 group (100 ng/mL LPS treatment for 4 h), and tolerance group (5 ng/mL LPS for 12 h followed by 100 ng/mL LPS for 4 h). The releases of inflammatory factors TNF-α and IL-6 were measured using ELISA. Western blotting and immunofluorescence assay were used to evaluate the distribution of autophagy-related proteins LC3 and P62, as well as TFEB in the cytoplasm and nucleus. Lentiviral overexpression of TFEB or siRNA-mediated knockdown of TFEB were performed to observe the changes in autophagy levels and bacterial clearance ability in the tolerant cells. Results‍　The cells in the tolerance group had significantly lower contents of TNF-α and IL-6, as well as reduced bacterial clearance ability (P<0.01), down-regulated LC3 expression while up-regulated P62 level, and decreased expression of TFEB in both the cytoplasm and nucleus (P<0.01) when compared with the cells of the LPS 100 group. Overexpression of TFEB significantly increased LC3 level, reduced P62 level, and enhanced bacterial clearance ability in the endotoxin-tolerant cells (P<0.01). In contrast, siRNA-mediated knockdown of TFEB had no significant impacts on LC3 and P62 expression levels or bacterial clearance ability. Conclusion ‍　Overexpression of TFEB can restore the autophagy of endotoxin-tolerant cells and enhance their bacterial clearance capacity, thereby alleviating the immunosuppressive state of sepsis. These findings suggest that TFEB holds promise as a potential therapeutic target for the prevention and treatment of sepsis.